The Ongole cattle: a versatile resource for the tropics - Narendra Nath, M.
(Fr, Es)
Ilus., 9 ref.
Keywords: GANADO BOVINO; CEBU; MEJORAMIENTO ANIMAL; INSEMINACION ARTIFICIAL; ADAPTACION; ZONA TROPICAL; PRODUCCION LECHERA; PRODUCCION CARNICA; ITALIA; VACUNO NELLORE; DE ZOOTECNIA